A New Model of Continuous Improvement in Total Quality Management from an Islamic Perspective - Afroza Bulbul Afrin; Rafikul Islam; Rodrigue Ancelot Harvey Fontaine; Md. Yousuf Ali; Mizanur Rahman (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2024)
Volume: 24 No: 1 (page: 129–149)